Easing the commute : the impact of affordable public transport on apprentice mobility - Langen, Henrika [Verfasser]; Dörsam, Michael [Verfasser] (My University, 2025)
„This paper examines how improved public transportation affordability, resulting from the introduction of the so-called Deutschlandticket, affected the commuting choices of newly commencing apprentices in Germany. Introduced in May 2023, the Deutschlandticket offers nationwide access to local and regional public transport at a flat monthly rate, replacing a previously fragmented fare system and substantially reducing commuting costs, particularly for commutes across transport association boundaries. Using administrative register data on apprenticeship contracts and detailed Deutschlandticket fare information, we assess changes in commuting patterns among new apprentices between 2022 and 2023. Our difference-in-differences analyses show that the Deutschlandticket led to a significant increase of around 21% in commutes on inter-transport-association routes, especially among older apprentices, those with lower school-leaving certificates, and those in certain training occupations. In contrast, we find no significant effect of region-specific Deutschlandticket-related cost savings on commuting distances within single transport associations. Our findings suggest that by reducing financial and informational barriers, the Deutschlandticket expanded access to apprenticeship opportunities and may have helped alleviate regional mismatches, without increasing commuting distances or requiring relocation.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.3.3 Mobilität; 370; Berufsausbildung; Auszubildender; Ausbildungsmobilität; Mobilitätsforschung; Öffentlicher Personennahverkehr; Kosten; Regionale Disparität